Severe pancytopenia at the presentation of Imerslund-Gräsbeck syndrome in a 23-month-old Italian boy - Francesca Di Sario; Francesca Piloni; Francesco Gasparini; Eleonora Serpetti; Barbara Bruschi; Paola Coccia; Maria Elena Lionetti; Simona Gatti (BMC, 2024)
Abstract Background Imerslund-Gräsbeck syndrome (IGS) is a rare autosomal recessive disorder characterized by megaloblastic anemia due to selective cobalamin malabsorption and benign proteinuria. IGS is caused by a disfunction of the cubam receptor, which mediates the reabsorption of cobalamin in the ileum and the reuptake of albumin in renal proximal tubules. Case presentation We describe the case of a 23-month-old-italian infant presenting with severe pancytopenia and failure to thrive in whom the diagnosis of IGS was made and vitamin B12 replacement therapy was resolutive. Genetic analysis (NGS with CNV analysis including 214 genes involved in bone marrow failure and anemia), showed the presence of two pathogenetic variants in the AMN gene (c-208-2 A > G and c.1006 + 34_1007-31del). These variants have been previously described in the literature, but their combination has never been reported. Conclusions Imerslund-Gräsbeck syndrome should be considered in the differential diagnosis of children with severe pancytopenia even in those without neurological involvement. This case emphasizes the importance of an early diagnosis and prompt treatment, to prevent irreversible neurological injury.